EFEKTIFITAS PENERAPAN UNDANG-UNDANG FIDUSIA TERHADAP PERJANJIAN KREDIT DENGAN JAMINAN KENDARAAN BERMOTOR - alip rahman (Hukum Responsif, 2015)
ABSTRACTThe presence of a wide range of financial institutions is a form of progress in community economic development, Fiduciary itself is an old term that has been known in the Indonesian language. According to Law No. 42 of 1999 About Fiducia is also called "handover of property rigths in trust". Contructions fiduciary of property rights on goods belonging to the debtor to the creditor being physical control over the goods that remain in debtors (constitutum Possesorium) with the proviso that when borrowers repay their debts, then creditors must restore the property rights over the goods to the debtor , How is the implementation of the provision of credit to the  motor vehicle  laws pertaining of fiduciary?. and how is the settlement of bad loans againts collateral of motor vehicles with fiduciary?. The method used to solve this problem is a normative juridical approach is the approach to the understanding of the science of law or juridical aspects of the effective  credit agreement with the guarantee of a motor vehicle. Bank in providing pasilitas credit to customers (borrowers) should pay attention to in terms of prudence and the extension of credit by the bank to the debtor does not just happen, but it should do the information on prospective debtors by using some of the principles, with the aim of reducing the risks that will occur at a later time. The steps taken in securing bank credit, in essence, can be classified into two, namely the securing of preventive and repressive security. Preventive security safeguards are taken to prevent the credit crunch. While the repressive security safeguards are taken to complete the credits have experienced ketidaklancaran or congestion (debius) .With this, the credit protection is essentially to minimize the risk, even at eliminating the risks that may arise or has arisen or occurred. Keywords: Effectiveness, the Credit Agreement, Motor Vehic